Alcohol trajectories and subsequent risk for opioid misuse in a cohort of urban adolescents. Issue 4 (2nd October 2021) - Thrul, Johannes; Reboussin, Beth A.; Rabinowitz, Jill A.; Maher, Brion S.; Ialongo, Nicholas S.
Abstract: Background: The opioid epidemic is a public health emergency in the US. Alcohol is the most widely used addictive substance among all age groups; however, the contribution of different alcohol use trajectories throughout adolescence and young adulthood to the development of opioid misuse in young adulthood among urban minority youth has not been investigated. Methods: Data are from a study of 580 youth (85% African American, 67% low SES) residing in Baltimore City followed from ages 6–26. Alcohol trajectories were identified between ages 14 and 26 using group-based trajectory modeling. Opioid misuse was defined as using opioid painkillers without a prescription or using heroin between ages 19 and 26. Opioid misuse outcomes were also investigated separately. Logistic regression examined associations of alcohol trajectories with opioid misuse in young adulthood adjusting for socio-demographics, early use of tobacco and cannabis, neighborhood, and peer factors. Results: Six alcohol use trajectories were identified: Young adult increasing (21.4%), adult increasing (19.1%), abstaining (19.1%), experimenting (15.3%), adolescent increasing (14.8%), and adolescent limited (10.2%). In models fully adjusted for covariates, relative to the abstaining trajectory, the adolescent increasing trajectory was associated with an elevated risk of opioid misuse (aOR = 3.3, 95%CI = 1.4, 7.8) and prescription opioid misuse (aOR = 3.9, 95%CI = 1.4, 10.8) in young adulthood. Conclusions: Escalating alcohol use in adolescence and young adulthood is associated with an elevated risk of opioid misuse in young adulthood in a cohort of predominantly African American and socio-economically disadvantaged young people. Tailored interventions should target high levels of alcohol use during these developmental periods to reduce risk for opioid misuse among disadvantaged youth.